Compromise and complicity in international student mobility: the ethnographic case of Indian medical students at a Chinese university. Issue 5 (3rd September 2018) - Yang, Peidong
ABSTRACT: Existing scholarship on international student mobility (ISM) often draws on Bourdieu to interpret such mobility as a strategy of capital conversion used by privileged classes to reproduce their social advantage. This perspective stems from and also reinforces a rationalistic interpretation of student mobility. A shift of focus to interAsian educational mobilities involving non-elite individuals and institutions can reveal logics of behavior and of social interaction that are at discrepancy with the dominant perspective, thereby advancing the theorization of educational mobilities. This paper examines a case of Indian youths of less affluent backgrounds pursuing English-medium medical degrees (MBBS) at a provincial university in China. Through ethnography, the paper illustrates how various parties – individual, organizational and institutional – to this somewhat 'unlikely' project of knowledge mobility follow the discrepant logics of compromise and complicity to seek to realize their educational desires, social aspirations, and organizational objectives amidst realities of class disadvantage and resource inadequacy.